Amyloid-β Inhibiting Peptides: An Innovative Strategy for Alzheimer’s Disease Treatment - Sajjad Molavipordanjani; Solmaz Mojarad-Jabali (Research in Molecular Medicine)
Alzheimer’s disease (AD), the most common neurodegenerative disorder, is characterized by the accumulation of amyloid-β (Aβ) plaques, leading to progressive cognitive decline. Targeting Aβ aggregation has become a major therapeutic focus, and peptide-based inhibitors have emerged as a promising approach due to their ability to specifically bind to Aβ and prevent its toxic oligomerization and fibril formation. This review discusses the advancements in Aβ-inhibiting peptides, including those derived from the Aβ sequence, as well as novel peptides discovered through phage display and mirror-image phage display technologies. These peptides offer significant advantages such as high selectivity and lower neurotoxicity, making them attractive candidates for therapeutic development. However, critical challenges—such as enzymatic degradation, poor blood-brain barrier (BBB) penetration, and the tendency for self-aggregation—have limited their clinical application. To overcome these barriers, recent innovations such as the incorporation of D-amino acids, cyclization, and retro-inverso modifications have improved peptide stability and bioavailability. Despite these improvements, further research is essential to optimize peptide design, enhance BBB permeability, and ensure long-term efficacy. This review emphasizes the importance of rational peptide design and the development of advanced delivery systems to address these limitations. By refining the molecular interactions and pharmacokinetic properties of Aβ-inhibiting peptides, future studies could significantly enhance their therapeutic potential. Ultimately, these efforts aim to advance peptide-based treatments through clinical trials and bring about meaningful progress in AD therapy.